Quantum oscillations in a stack of superconducting cylinders in a magnetic field: crossover from the Aharonov–Bohm to the Little–Parks regime - Gvozdikov, V.M. (Физика низких температур, 2000)
The Aharonov–Bohm (AB) oscillations of the free energy, critical temperature Tc, magnetization M, and magnetic susceptibility χ as functions of the magnetic flux Φ through the hollow in a stack of mesoscopic superconducting cylinders are studied both analytically and numerically. The shape of these oscillations at low temperature T and small level broadening ν is generally nonsinusoidal and has singularities that depend on the superconducting order parameter Δ and stacking sequence. The period of the oscillations is equal to the normal flux quantum Φ₀. The harmonic amplitudes of the AB oscillations decrease exponentially if the diameter 2R of the cylinders becomes greater than the coherence length. Further increase of R results in a complete suppression of the AB oscillations and the development of parabolic Little–Parks (LP) oscillations of Tc(Φ) with half the period, Φs=Φ₀/2. Therefore a crossover from the AB to LP oscillations takes place as the diameter 2R is increased. It is shown that the temperature behavior of the magnetic susceptibility below the superconducting transition is χ ∝ exp(−T/T*), where T*=ℏv₀/2π²R (v₀ is the Fermi velocity, and ℏ is Planck’s constant). Such dependence of χ(T) has been observed recently in Ag wires coated with thin Nb layers in a weak external field [R. Frassanito et al., Czech. J. Phys. 46, 2317 (1996)].